China’s energy transition: preliminary results and challenges for the future - L. Xialan (Проблемы постсоветского пространства)
The article is devoted to the study of China’s energy transition policy and the prospects for its implementation. As the world’s second largest economy, the People’s Republic of China has become an important part of the global energy market in recent years. In the process of industrialization and economic growth, the Chinese economy plays an important and positive role in maintaining the world’s energy security. In connection with the gradual slowdown in the growth of the Chinese economy, the full implementation of the Paris Agreement, as well as the transformation and modernization of the global energy structure, the Chinese side proposed a new strategy for energy transition and energy security. In 2020, China announced a desire to reduce carbon emissions and achieve carbon neutrality. Despite the fact that China’s own coal dominates in the structure of China’s energy balance, the emphasis is on identifying the role of oil and gas in the modernization of the energy system. The features of China’s energy production and consumption structure are emphasized, in which natural gas can become an auxiliary and transitional energy source during its transformation of the energy system. The article discusses the main documents that define the energy transition. The preliminary results of China’s implementation of the new energy policy have been summed up. It is concluded that energy saving and efficiency improvement are the primary objectives of China’s modern energy strategy, as well as important measures to reduce carbon dioxide emissions.